The Measurement of Usability Using USE Questionnaire on the Google Classroom Application as E-learning Media (A Case study: SMK Negeri 1 Bandung) - Saniatu Nisail Jannah; Ade Sobandi; Suwatno Suwatno (Teknodika, 2020)
The Pandemic Covid-19 has changed various aspects of human life currently, especially in education. In this Covid-19 pandemic, E-learning users have been increased. Work from home policy from government generates the whole process of learning activities in SMK Negeri 1 Bandung been substituted by an online learning model. E-Learning platform that is widely used is Google Classroom. As a widely used platform, it is necessary to measure the usability of this application. Usability can be measured from the results of the percentage of eligibility obtained based on a questionnaire distributed to users, the questionnaire applied the USE questionnaire method, which contained a series of statements that have been grouped into several aspects of use, i.e., ease of use, ease of learning, satisfaction, and usefulness. The results obtained for each aspect of usability were the ease of use aspect with 80% of eligibility, the ease of learning aspect with 83% of eligibility, satisfaction with 81% of eligibility, and ease of use with 81% of eligibility. Overall the results of usability testing obtained 81% of eligibility. It means that Google Classroom application is very feasible to be used by teachers since this application is easy to use, easy to learn, useful as e - learning media.